Human-Computer Interaction: Applications and Services 15th International Conference, HCI International 2013, Las Vegas, NV, USA, July 21-26, 2013, Proceedings, Part II - Kurosu, Masaaki; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The five-volume set LNCS 8004--8008 constitutes the refereed proceedings of the 15th International Conference on Human-Computer Interaction, HCII 2013, held in Las Vegas, NV, USA in July 2013. The total of 1666 papers and 303 posters presented at the HCII 2013 conferences was carefully reviewed and selected from 5210 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers accepted for presentation thoroughly cover the entire field of Human-Computer Interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. This volume contains papers in the thematic area of human-computer Interaction, addressing the following major topics: HCI in healthcare; games and gamification; HCI in learning and education; in-vehicle Interaction.
HCI in Healthcare -- Software Engineering in Telehealth, an Extension of Sana Mobile Applied to the Process of a Routine Hospital.-Cross Cultural Design Considerations in HealthCare -- Designing Copresent Cycling Experience -- Achieving Electronic Health Record Access from the Cloud -- User Requirements for the Development of Smartphone Self-reporting Applications in Healthcare -- Electronic Health Records: A Case Study of an Implementation -- Healthcare Interoperability: CDA Documents Consolidation Using Transport Record Summary (TRS) Construction -- Designing, Implementing and Testing a Mobile Application to Assist with Pediatric-to-Adult Health Care Transition -- Study on Relationship between Foot Pressure Pattern and Hallux Valgus (HV) Progression -- A Server-Based System Supporting Motor Learning through Real-Time and Reflective Learning Activities -- Usability Evaluation of a Voluntary Patient Safety Reporting System: Understanding the Difference between Predicted and Observed Time Values by Retrospective Think-Aloud Protocols -- Usability in RFP’s: The Current Practice and Outline for the Future -- Design and Interface Considerations for Web-Enabled Data Management in Civil Infrastructure Health Monitoring -- Empowering Young Adolescents to Choose the Healthy Lifestyle: A Persuasive Intervention Using Mobile Phones -- Telemedicine and Design: Relationships that Create Opportunities -- A Proposal of the New System Model for Nursing Skill Learning Based on Cognition and Technique -- Usability Testing for e-health Application: A Case Study for Sana/Open MRS -- Introducing Emotional Interfaces to Healthcare Systems -- Human Adequate Lighting in Optimal Healing Environments – Measuring Non-visual Light Effects of a LED Light Source According to German Draft Pre-standard DIN SPEC 5031-100:2012 -- Discussion of Some Challenges Concerning Biomedical Ontologies -- Web Searching for Health Information: An Observational Study to Explore Users’ Emotions -- Native Apps versus Web Apps: Which Is Best for Healthcare Applications? -- Experiences with Arthron for Live Surgery Transmission in Brazilian Telemedicine University Network -- User Experience in Public Information Service Design for Smart Life -- The Proposal of the Remote Consultation Service System Using the Outline Function for Consultation -- Games and Gamification -- Design Guidelines for Audio Games -- SWord: A Concept Application for Mitigating Internet Terminology Anxiety -- Extreme Motion Based Interaction for Enhancing Mobile Game Experience -- Influence of Gaming Display and Controller on Perceived Characteristics, Perceived Interactivity, Presence, and Discomfort -- A Cross-Cultural Study of Playing Simple Economic Games Online with Humans and Virtual Humans -- Best Practices for Using Enterprise Gamification to Engage Employees and Customers -- Gamifying Support -- The Motivational GPS: Would a Rat Press a Lever to Get a Badge? -- Designing Serious Videogames through Concept Maps -- The Business Love Triangle- Smartphones, Gamification, and Social Collaboration -- Building Internal Enthusiasm for Gamification in Your Organization -- Navigation Experiences – A Case Study of Riders Accessing an Orientation Game via Smartphones -- HCI in Learning and Education -- Evaluating Engagement Physiologically and Knowledge Retention Subjectively through Two Different Learning Techniques -- A New E-learning System Focusing on Emotional Aspect Using Biological Signals -- A Framework to Support Social-Collaborative Personalized e-Learning -- Challenges for Contextualizing Language Learning: Supporting Cultural Integration -- Usability of a Social Network as a Collaborative Learning Platform Tool for Medical Students -- Refining Rules Learning Using Evolutionary PD -- Sound to Sight: The Effects of Self-generated Visualization on Music Sight-Singing as an Alternate Learning Interface for Music Education within a Web-Based Environment -- Evaluation of Computer Algebra Systems Using Fuzzy AHP at the Universities of Cyprus -- Evaluation of an Information Delivery System for Hearing Impairments at a School for Deaf -- Examining the Role of Contextual Exercises and Adaptive Expertise on CAD Model Creation Procedures -- Personality and Emotion as Determinants of the Learning Experience: How Affective Behavior Interacts with Various Components of the Learning Process -- Innovation in Learning – The Use of Avatar for Sign Language -- A Teacher Model to Speed Up the Process of Building Courses -- Development of Push-Based English Words Learning System by Using E-Mail Service -- E-learning: The Power Source of Transforming the Learning Experience in an ODL Landscape -- Mobile Inquiry-Based Learning: A Study of Collaborative Scaffolding and Performance -- A Comparative Evaluation of Podcasting-Based and Mobile-Based Material Distribution Systems in Foreign Language Teaching -- Recommendation of Collaborative Activities in E-learning Environments -- Nature Sound Ensemble Learning in Narrative-Episode Creation with Pictures -- Private Cloud Cooperation Framework for Reducing the Earthquake Damage on e-Learning Environment -- Design and Evaluation of Training System for Numerical Calculation Using Questions in SPI2 -- Zoom Interface with Dynamic Thumbnails Providing Learners with Companionship through Videostreaming -- In-Vehicle Interaction -- WheelSense: Enabling Tangible Gestures on the Steering Wheel for In-Car Natural Interaction -- Reducing Speeding Behavior in Young Drivers Using a Persuasive Mobile Application -- Auditory and Head-Up Displays in Vehicles -- Anti-Bump: A Bump/Pothole Monitoring and Broadcasting System for Driver Awareness -- Emotion and Emotion Regulation Considerations for Speech-Based In-Vehicle Interfaces -- Adaptations in Driving Efficiency with Electric Vehicles -- In-Car Information Systems: Matching and Mismatching Personality of Driver with Personality of Car Voice -- Subjective Ratings in an Ergonomic Engineering Process Using the Example of an In-Vehicle Information System -- Ergonomics Design on Expert Convenience of Voice-Based Interface for Vehicle’s AV Systems -- The Timeframe of Adaptation to Electric Vehicle Range -- Exploring Electric Driving Pleasure – The BMW EV Pilot Projects -- Single-Handed Driving System with Kinect -- Mobile App Support for Electric Vehicle Drivers: A Review of Today’s Marketplace and Future Directions -- Proposal for Driver Distraction Indexes Using Biological Signals Including Eye Tracking -- Ergonomics Design with Novice Elicitation on an Auditory-Only In-Vehicle Speech System.
Keywords: User interfaces (Computer systems).; Application software; Education—Data processing; Computers and civilization; Information storage and retrieval; User Interfaces and Human Computer Interaction; Computer Applications; Computers and Education; Computers and Society; Information Systems Applications (incl. Internet).; Information Storage and Retrieval